ANALISIS STILISTIKA PADA PUISI-PUISI TERPILIH KARYA TOTO SUDARTO BACHTIAR - Yulsafli, Yulsafli; Nurliza, Eli; Azkiya, Mukarramatul (Jurnal Dedikasi Pendidikan, 2024)
The purpose of this study is to analyze the language style contained in selected poems by Toto Sudarto Bachtiar. The research method used is qualitative method by describing the facts and identifying the appropriate language style. The data collection techniques used in this research are literature study, listening and note-taking techniques. The results of the analysis show, (1) Poem Gadis Peminta-minta, there are three uses of language style, namely, personification, metaphor, hyperbole. (2) Poem Unknown Hero, there are eight language styles in this poem including metaphor, personification, hyperbole, epanalipsis, alliteration, parallelism, ellipsis, contradiction. (3) Poem Ibukota Senja, there are nine styles including personification, hyperbole, simile, metonimia, tautology, apostrophe, tautology, oxymoron, repetition